Effect of training and structured medication review on medication appropriateness in nursing home residents and on cooperation between health care professionals: the InTherAKT study protocol. Issue 1 (December 2017) - Mahlknecht, Angelika; Nestler, Nadja; Bauer, Ulrike; Schüßler, Nadine; Schuler, Jochen; Scharer, Sebastian; Becker, Ralf; Waltering, Isabel; Hempel, Georg; Schwalbe, Oliver; Flamm, Maria; Osterbrink, Jürgen
Abstract Background Pharmacotherapy in residents of nursing homes is critical due to the special vulnerability of this population. Medical care and interprofessional communication in nursing homes are often uncoordinated. As a consequence, polypharmacy and inappropriate medication use are common and may lead to hospitalizations and health hazards. The aim of this study is to optimize communication between the involved professional groups by specific training and by establishing a structured medication review process, and to improve medication appropriateness and patient-relevant health outcomes for residents of nursing homes. Methods/Design The trial is designed as single-arm study. It involves 300 nursing home residents aged ≥ 65 years and the members of the different professional groups practising in nursing home care (15–20 general practitioners, nurses, pharmacists). The intervention consists of interprofessional education on safe medication use in geriatric patients, and a systematic interprofessional therapy check (recording, reviewing and adapting the medication of the participating residents by means of a specific online platform). The intervention period is divided into two phases; total project period is 3 years. Primary outcome measure is the change in medication appropriateness according to the Medication Appropriateness Index. Secondary outcomes are cognitive performance, occurrence of delirium, agitation, tendency of falls, total number of drugs, number of potentially dangerous drug-drug interactions and appropriateness of recorded analgesic therapy regimens according to the Medication Appropriateness Index. Data are collected at t0 (before the start of the intervention), t1 (after the first intervention period) and t2 (after the second intervention period). Cooperation and communication between the professional groups are investigated twice by qualitative interviews. Discussion The project aims to establish a structured system for monitoring of drug therapy in nursing home residents. The newly developed online platform is designed to systematize and to improve the communication between the professional groups and, thus, to enhance quality and safety of drug therapy. Limitations of the study are the lack of a control group and the non-randomly recruited study sample. Trial registration DRKS Data Management, DRKS-ID:DRKS00007900